ABOUT THE NAMES FOR ‘PEPPER’ IN VAL DE XÁLIMA (CÁCERES): A(I)XÍN AND PIMENTU - Flores, Ana Alicia Manso [UNESP] (Universidad de la Rioja, 2022)
In Val de Xálima, an area located in the northwest of Extremadura, the usual language of communication is Fala, Valego, or Xalimego. The bibliography ascribes it to the Galician-Portuguese group and points to the influence of neighboring languages and varieties. Studies on its lexicon reveal that it is a key piece, with the capacity to broaden the understanding of the histories of the languages of the Western Iberian Peninsula. Thus, this article proposes the study of the names used for the concept 'pepper': a(i)xín and pimentu. In this case, the language of introduction is not clear; for this reason, the results will be compared, for both lexical bases, from the documentation extracted from dictionaries and lexicographical corpora of the languages and varieties related to Fala: Spanish, Portuguese, Galician, Astur-Leonese, and Extremadura fala.
SOBRE LOS NOMBRES PARA EL ‘PIMIENTO’ EN EL VAL DE XÁLIMA (CÁCERES): A(I)XÍN Y PIMENTU
SUR LES NOMS DU ‘POIVRON’ DANS LE VAL DE XÁLIMA (CÁCERES): A(I)XÍN ET PIMENTU
Keywords: chronology; Fala; lexicon; origin; pepper; Val de Xálima